Analisis Muatan Nilai Nasionalisme Dalam Film Serangan Fajar Karya Arifin C. Noer - Arif Rizki Rahmadhani; Tjipto Sumadi; Fauzi Abdillah (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2022)
This study aims to determine the values of nationalism in Arifin C. Noer's Serangan Fajar film and to find out the nationalism values depicted in Arifin C. Noer's Serangan Fajar film, Arifin C. Noer's Serangan Fajar film. The research approach used in this research is qualitative using a descriptive method. Collecting data in this study using documentation techniques from the film Serangan Fajar, interviewing informants to complete it. Interviews were conducted with 2 (two) informants, namely, students of Building Engineering Education, State University of Jakarta and students of Sociology Education, Universitas Pendidikan Indonesia. The reason for choosing the informant was because he had watched the film Serangan Fajar and was willing to be interviewed, and 1 (one) key informant, namely a Teaching Practitioner at the Akademi Film Yogyakarta (AFY), and carried out the confirmation process to an expert, namely a lecturer in History Education UNJ. This study found that the content of the values of nationalism in the film Serangan Fajar, namely (1) love for the homeland and nation, (2) willing to sacrifice, (3) fight for the nation and state, (4) unity and integrity, (5) proud with the nation, (6) prioritize & defend the homeland. The values of nationalism implemented in the film Serangan Fajar are explained through the presence of scenes, dialogues, attitudes and thoughts of the characters, and descriptions of events that occur in the film.The conclusion of this research is that there are six values of nationalism contained in the film Serangan Fajar by Arifin C. Noer, namely (1) love for the homeland and nation, (2) willing to sacrifice, (3) fighting for the nation and state, (4) unity and integrity. unity, (5) proud of the nation, (6) prioritizes & defends the homeland. The values of nationalism are depicted in Serangan Fajar film through scenes, dialogues, attitudes and thoughts of the characters, as well as descriptions of events that occur in the film.Keywords: Nationalism, Fajar Attack Film, Attitude